2018
DOI: 10.1123/jsr.2016-0143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hip Strengthening on Neuromuscular Control, Hip Strength, and Self-Reported Functional Deficits in Individuals With Chronic Ankle Instability

Abstract: Improved clinical and patient-reported outcomes in the training group suggest hip strengthening is beneficial in the management and prevention of recurrent symptoms associated with CAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 39 publications
2
39
0
1
Order By: Relevance
“…This functional approach may lead to additional benefits linked to the recruitment of larger muscle groups during multijoint exercises, which could positively influence the balance strategies of patients with CAI. 15 These results agree with those of Donovan et al, 33 who developed a multicomponent training protocol for patients with CAI and reported benefits in DFROM and balance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This functional approach may lead to additional benefits linked to the recruitment of larger muscle groups during multijoint exercises, which could positively influence the balance strategies of patients with CAI. 15 These results agree with those of Donovan et al, 33 who developed a multicomponent training protocol for patients with CAI and reported benefits in DFROM and balance.…”
Section: Discussionsupporting
confidence: 90%
“…Although some authors have reported on core training, hip strengthening, ankle-joint stretching, and peroneal strengthening for improving ankle instability, only in the past few years have combinations of these training options been evaluated. 15,16 Our hypothesis was that taking part in a CrossFit-based intervention that included self-mobilization techniques would improve DFROM, dynamic postural control, and self-reported instability of patients with CAI.…”
mentioning
confidence: 99%
“…According to our study results, the overall, anterior, posterolateral and posteromedial stability indices of right and left leg, as well as the VJT and IAT scores, showed significant differences in the female athletes with DKV after 8-week plyometric training. One of the possible reasons for the improvement in their balance after plyometric training is the increase in exercise pressure by this training which is created by facilitating and synchronizing the large and fast-twitch motor units [23], stimulation of muscle spindles [24], reduction of Golgi tendon organs' inhibitory effect, and the increase in the coordination of muscles involved in co-contraction activities [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians treating patients with LAS or CAI are encouraged to assess hip-strength impairments and dedicate time to resolving deficits with therapeutic exercise. 35 Two groups 36,37 have investigated hip strengthening in patients with CAI, and both reported improvements in clinical outcomes. Smith et al 37 examined the effects on dynamic postural control, noting that hip strengthening improved the Star Excursion Balance Test scores of patients with CAI.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…35 Two groups 36,37 have investigated hip strengthening in patients with CAI, and both reported improvements in clinical outcomes. Smith et al 37 examined the effects on dynamic postural control, noting that hip strengthening improved the Star Excursion Balance Test scores of patients with CAI. We did not find an association between isometric hip strength and dynamic stability in individuals with CAI, which suggests that increasing isometric hip-muscle strength may not be an effective means of enhancing dynamic stability.…”
Section: Clinical Applicationmentioning
confidence: 99%